2018
DOI: 10.1021/acsami.8b16013
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Visible-Light-Driven Photocatalytic Hydrogen Evolution on Phosphorus-Doped Covalent Triazine-Based Frameworks

Abstract: Seeking efficient visible-light-driven photocatalysts for water splitting to produce H 2 has attracted much attention. Chemical doping is an effective strategy to enhance photocatalytic performance. Herein, we reported phosphorus-doped covalent triazine-based frameworks (CTFs) for photocatalytic H 2 evolution. Phosphorus-doped CTFs were fabricated by a facile thermal treatment using easily available red phosphorus as the external phosphorus species. The introduction of phosphorus atoms into the frameworks modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 42 publications
0
62
0
Order By: Relevance
“…Under AM 1.5 G irradiation and at 0.3 V versus RHE, the three 2D conjugated polymers on fluorine‐doped tin oxide (FTO) electrodes show photocurrents of ≈5.5 µA cm −2 for 2D CCP‐Th, ≈2.8 µA cm −2 for 2D CCP‐BD, and ≈0.06 µA cm −2 for 2D CN COF‐B ( Figure a,b). Moreover, 2D CCP‐Th achieves a photocurrent of ≈7.9 µA cm −2 at 0 V versus RHE, which exceeds those of the reported 2D COFs (0.09–6.0 µA cm −2 ) [ 8,9,13,27–32 ] and most carbon nitride materials (g‐C 3 N 4 , 0.3–1.2 µA cm −2 ) (Table S6, Supporting Information). [ 33–37 ] As a key parameter to evaluate the intrinsic PEC performance of photoelectrode materials, the incident‐photon‐to‐current efficiency (IPCE) was measured (Figure S30, Supporting Information).…”
Section: Figurementioning
confidence: 79%
See 1 more Smart Citation
“…Under AM 1.5 G irradiation and at 0.3 V versus RHE, the three 2D conjugated polymers on fluorine‐doped tin oxide (FTO) electrodes show photocurrents of ≈5.5 µA cm −2 for 2D CCP‐Th, ≈2.8 µA cm −2 for 2D CCP‐BD, and ≈0.06 µA cm −2 for 2D CN COF‐B ( Figure a,b). Moreover, 2D CCP‐Th achieves a photocurrent of ≈7.9 µA cm −2 at 0 V versus RHE, which exceeds those of the reported 2D COFs (0.09–6.0 µA cm −2 ) [ 8,9,13,27–32 ] and most carbon nitride materials (g‐C 3 N 4 , 0.3–1.2 µA cm −2 ) (Table S6, Supporting Information). [ 33–37 ] As a key parameter to evaluate the intrinsic PEC performance of photoelectrode materials, the incident‐photon‐to‐current efficiency (IPCE) was measured (Figure S30, Supporting Information).…”
Section: Figurementioning
confidence: 79%
“…Benefitting from the D–A structure, the bithiophene‐bridged 2D CCP‐Th shows a much narrower optical energy bandgap (2.04 eV), a higher‐lying LUMO energy level (−3.41 eV), and higher charge separation and transport than those of biphenyl‐bridged 2D CCP‐BD and 2D CN COF‐B. Therefore, as the cathode material for PEC water reduction, 2D CCP‐Th demonstrates a superb saturated photocurrent density up to 5.5 µA cm −2 at 0.3 V and 7.9 µA cm −2 at 0 V versus reversible hydrogen electrode (RHE), which is superior to the reported 2D COFs [ 8,9,13,27–32 ] and most carbon nitride (g‐C 3 N 4 ) materials (0.09–6.0 µA cm −2 ) [ 33–37 ] (Table S6, Supporting Information). Furthermore, density functional theory (DFT) simulations further suggest that the sulfur atoms in the thiophene as well as the cyano groups at the vinylene linkage serve as the active sites for water reduction.…”
Section: Figurementioning
confidence: 99%
“…Together with the nitrogen rich backbone, tunable band gap and energy levels, this makes CTFs interesting candidates for photocatalytic CO2 reduction and water splitting. 14,15,177,182,184,[189][190][191][192] This feasibility was initially predicted by calculations and it was observed that the band gap of these semiconducting materials should decrease with decreasing nitrogen content in the structures. 193 At the same time, a smaller pore size was calculated to induce a larger band gap by quantum confinement effects.…”
Section: <Table 3>mentioning
confidence: 86%
“…Heteroatom substitution vary the charge polarity of COFs efficiently and then affects the charges transfer and the band structures of polymers. Both sulfur‐doped CTFs (CTFS 10 ) and phosphorus‐doped CTFs (P 5 CTF‐1) delivered higher photocatalytic hydrogen activity than the pristine CTFs.…”
Section: Photochemical Applicationsmentioning
confidence: 99%